Responding to the Challenges of Adult Refugee Language Education through Action Research - Evdokia Karavas; Iakovou, Maria; Mitsikopoulou, Bessie (International Journal of Learner Diversity and Identities, 2021)
Arguing that action research is an appropriate methodological framework in integration projects owing to the unpredictable challenges associated with the particular group of learners, this article focuses on the process ofdesigning, implementing, evaluating, and redesigning a Greek and English language program for the purposes of the“Curing the Limbo” project. It highlights crucial decisions that were made and tested with the involvement of relevantstakeholders in order to respond to the imminent communicative needs of adult refugees, leading to the goal of inclusiveintegration. The article also addresses the challenges faced during the COVID-19 pandemic lockdowns